European multiple sclerosis risk variants in the south Asian population. (October 2016) - Pandit, Lekha; Ban, Maria; Beecham, Ashley Harris; McCauley, Jacob L; Sawcer, Stephen; D'Cunha, Anitha; Malli, Chaitra; Malik, Omar
Background: In less than a decade, genomewide association studies have identified over 100 single-nucleotide variants that are associated with increased risk of developing multiple sclerosis. However, since these studies have focused almost exclusively on European populations, it is unclear what role these variants might play in determining risk in other ethnic groups. Objective: To assess the effects of European multiple sclerosis–associated risk variants in the south Asian population. Methods: Using a combination of chip-based genotyping and next-generation sequencing, we have assessed 109 European-associated variants in a total of 270 cases and 555 controls from the south Asian population. Results: We found that two-thirds of the tested variants (72/109) showed over representation of the European risk allele in south Asian cases ( p  < 0.0003). In the rest of the Immunochip array, the most associated variant was rs7318477 which maps close to TNFSF13B, the gene for the B-cell-related protein BAFF. Conclusion: Our data indicate substantial overlap in genetic risk architecture between Europeans and south Asians and suggest that the aetiology of the disease may be largely independent of ethnicity.